EFFECT OF LIVEWEIGHT ON HAEMOLYMPH BIOCHEMICAL AND HORMONAL PROFILE OF GIANT AFRICAN LAND SNAIL (ARCHACHATINA MARGINATA) UNDER TROPICAL ENVIRONMENT - Ajiboye , Oluwatosin; Abiona, John Adesanya; Oke, Oyegunle Emmanuel; Onagbesan, Okanlawon Muhammed (Polish Journal of Natural Sciences, 2024)
Demand for giant African Land snail (Archachatina marginata) is on the increase in recent years, but not much is known about the health indicators of this animal under indoor or intensive rearing. The aim of the study was to determine the effect of liveweight on biochemical and physiological parameters of Archachatina marginata and to establish reference ranges for these parameters. Snails used were assigned to 3 groups of 20 snails each based on their liveweight. Haemolymph collected was analyzed for biochemical, hormonal and selected minerals. Result showed that the effect of liveweight was not significant (P > 0.05) for Total protein (TP), Triglyceride (Trig), Alanine transaminase (ALT) and Glucose (Glu). However, Liveweight had significant effect (p < 0.05) on Albumin (Alb), Aspartate transaminase (AST), Cholesterol (Chl) and Creatinine (Crt). For hormonal profile, only T4 was significantly influenced (p < 0.05) by liveweight, while effect of liveweight was not significant on Triiodothyronine (T3), Follicle-stimulating hormone (FSH), Estradiol (E2) and Progesterone (P4). For haemolymph minerals, liveweight only had significant effect on Cu and Fe among others. Physiological profiles quantitatively recorded for each of liveweight groups by the the present standard protocols provide a reference basis to quantify physiological changes under different environmental conditions.